2022
DOI: 10.3390/genes13101717
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Jasmonate Induces Genes Involved in Linalool Accumulation and Increases the Content of Phenolics in Two Iranian Coriander (Coriandrum sativum L.) Ecotypes

Abstract: The medicinal herb coriander (Coriandrum sativum L.), with a high linalool (LIN) content, is widely recognized for its therapeutic benefits. As a novel report, the goals of this study were to determine how methyl jasmonate (MeJA) affects total phenolic content (TPC), LIN content, flavonoid content (TFC), and changes in gene expression involved in the linalool biosynthesis pathway (CsγTRPS and CsLINS). Our findings showed that, in comparison to the control samples, MeJA treatment substantially enhanced the TPC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The reaction was terminated by heating at 70 °C for 5 min, and the synthesized cDNA was stored at −20–42 °C for RT–PCR analysis. The whole process of RNA extraction and cDNA synthesis was accomplished according to the extraction and cDNA synthesis discussed in Kianersi et al [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The reaction was terminated by heating at 70 °C for 5 min, and the synthesized cDNA was stored at −20–42 °C for RT–PCR analysis. The whole process of RNA extraction and cDNA synthesis was accomplished according to the extraction and cDNA synthesis discussed in Kianersi et al [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Also, the highest expression of the studied genes and carvacrol content was observed in vulgare subspecies at 50 mM salt stress. The gene expression levels may be variable depending on the stress and plant species [ 69 ]. The higher expression of these genes in retort to moderate salinity stress may reverberate the elevation of phenolic monoterpenes such as carvacrol.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the preharvest treatment of coriander leaves with malic, oxalic and acetylsalicylic acids increases the polyphenolic content and hence the antioxidant activity of coriander extract [40]. Kianersi et al (2022) [41] report that a notable plant hormone, methyl jasmonate (MeJA), has been shown to impact the accumulation of these secondary metabolites by modulating signal transduction and defence gene expression. The study by Kianersi et al (2022) [42] further investigates the effects of MeJA on the expression of key genes involved in linalool and γ-terpinene biosynthesis, phenolic compound accumulation and linalool content in two Iranian Coriandrum sativum genotypes (Mashhad and Zanjan).…”
Section: Coriander Phenolicsmentioning
confidence: 99%
“…Kianersi et al (2022) [41] report that a notable plant hormone, methyl jasmonate (MeJA), has been shown to impact the accumulation of these secondary metabolites by modulating signal transduction and defence gene expression. The study by Kianersi et al (2022) [42] further investigates the effects of MeJA on the expression of key genes involved in linalool and γ-terpinene biosynthesis, phenolic compound accumulation and linalool content in two Iranian Coriandrum sativum genotypes (Mashhad and Zanjan). The study results indicate that MeJA treatment enhances the expression of the linalool synthase (CsLINS) and γ-terpinene synthase (CsγTRPS) genes, leading to the increased biosynthesis of linalool and total phenolic content in the two genotypes.…”
Section: Coriander Phenolicsmentioning
confidence: 99%